KANDUNGAN UNSUR HARA MAKRO PADA KOMPOS FIBER DAN TANDAN KOSONG KELAPA SAWIT (Elaeis guineensis Jacq.) - Herry Iswahyudi; M. Didi Iskandar (EnviroScienteae, 2023)
This research on Observing the content of macro nutrients in OPEFB and Fiber  compost  aims  to determine the levels of macro nutrients N, P, K, and C-Organic contained in the compost produced in this have a look at. The composting process used EM4 material and AC water to be a mixture of ingredients in composting. EFB and Fiber composted in this composting process were 2 Kg each. This composting process lasted for 31 days. After the compost was riped, the tests for the nutrient content of N, P, K, C-Organic, and C/N ratio were conducted in the laboratory. The results of the laboratory tests on OPEFB and Fiber with indicators of N, P, K, C-Organic and C/Nratio showed that there was a variation in yield between EFB compost and Fiber compost. It showed that the different of macronutrient content of OPEFB had a N value of 2.29%, P 0.18%, K 1.54%, C- Organic 41.83%, and a C/N ratio of 17.9. Fiber compost content has a value of N 1.47%, P 0.12%, K 2.04%, C-Organic 51.13%, and a C/N ratio of 34.8. The results of the laboratory tests showed that the OPEFB compost made in this research has complied with the requirements of SNI compost 19-7030-2004.